The E-Aspiration System as an Implementation of Public Participation from the Good Governance Perspective - Muhammad Anfasha Wirakusuma; Agus Riwanto (Varia Justicia, 2022)
This research aimed to examine democracy development using e-participation through the e-aspiration system applied in public services to realize the smart city in Magelang City. Magelang City Government has released a special mobile application called Magelang Cerdas. The ease of public services provided by the Magelang Cerdas application has created various features that promote e-participation. This refers to online public participation by utilizing information and communication technology and the smart city concept. The smart city is related to information and communication technology used in the social field. It could be realized by opening public participation in ensuring the democratic rights of every citizen through the e-aspiration. The goal was to capture people’s aspirations to increase their participation in influencing Magelang City development. This modern day the government should provide financial support for the technological developments. Therefore, public services should be provided through conventional and digital-based delivery, such as e-government, which reflects the principles of good governance. Digital-based services could fulfil people’s rights and obligations as citizens. As a result, the people would directly realize digital government according in the modern era. The ease of access in participation would also help the government follow the direction and needs of the people. In implementing the smart city concept, Therefore, this research examined the factors supporting and strengthening public participation in the smart city concept on the Good Gonvernance perspective.